Doping-induced structural phase transition in cobalt diselenide enables enhanced hydrogen evolution catalysis - Zheng, Ya-Rong; Wu, Ping; Gao, Min-Rui; Zhang, Xiao-Long; Gao, Fei-Yue; Ju, Huan-Xin; Wu, Rui; Gao, Qiang; You, Rui; Huang, Wei-Xin; Liu, Shou-Jie; Hu, Shan-Wei; et al. (Nature communications, 2018)
Transition metal dichalcogenide materials have been explored extensively as catalysts to negotiate the hydrogen evolution reaction, but they often run at a large excess thermodynamic cost. Although activating strategies, such as defects and composition engineering, have led to remarkable activity gains, there remains the requirement for better performance that aims for real device applications. We report here a phosphorus-doping-induced phase transition from cubic to orthorhombic phases in CoSe 2 . It has been found that the achieved orthorhombic CoSe 2 with appropriate phosphorus dopant (8 wt%) needs the lowest overpotential of 104 mV at 10 mA cm −2 in 1 M KOH, with onset potential as small as −31 mV. This catalyst demonstrates negligible activity decay after 20 h of operation. The striking catalysis performance can be attributed to the favorable electronic structure and local coordination environment created by this doping-induced structural phase transition strategy. Transition metal dichalcogenides represent an exciting class of earth-abundant hydrogen-from-water electrocatalysts, although low efficiencies limit commercialization. Here, authors present a doping strategy to induce a phase transition in cobalt selenide and boost H 2 -evolution performance.